2008
DOI: 10.1089/scd.2008.0023
|View full text |Cite
|
Sign up to set email alerts
|

Human Cord Blood Mononuclear Cells Decrease Cytokines and Inflammatory Cells in Acute Myocardial Infarction

Abstract: We investigated whether human umbilical cord blood mononuclear cells (HUCBC), which contain hematopoietic and mesenchymal progenitor cells, can limit myocardial cytokine expression and inflammatory cell infiltration in acute myocardial infarction. We permanently ligated the left coronary artery of rats and injected into the myocardium either Isolyte or 4 x 10(6) HUCBC in Isolyte and measured myocardial cytokines with antibody arrays at 2, 6, 12, 24, and 72 hours after infarction. We then measured with flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 44 publications
1
39
0
1
Order By: Relevance
“…hUCB stem cells have also been used experimentally in animal models of TBI. In some studies, transplanted cells derived from the mononuclear fraction of hUCB conferred neuroprotection by decreasing inflammation and brain tissue loss, promoting neurogenesis, and rescue of neurological dysfunctions (e.g., 11,41,78). Additionally, mesenchymal stem cells (MSCs) derived from hUCB promoted functional benefits by increasing angiogenesis and vasculogenesis (1,53,55).…”
Section: Stem Cell Transplantation In Tbimentioning
confidence: 99%
“…hUCB stem cells have also been used experimentally in animal models of TBI. In some studies, transplanted cells derived from the mononuclear fraction of hUCB conferred neuroprotection by decreasing inflammation and brain tissue loss, promoting neurogenesis, and rescue of neurological dysfunctions (e.g., 11,41,78). Additionally, mesenchymal stem cells (MSCs) derived from hUCB promoted functional benefits by increasing angiogenesis and vasculogenesis (1,53,55).…”
Section: Stem Cell Transplantation In Tbimentioning
confidence: 99%
“…Moreover, this paracrine action of hUCBC is increased 50 to 100% during severe hypoxia and in the presence of free oxygen radicals [20,24]. This paracrine action of hUCBC can suppress in the ischemic myocardium the inflammatory cytokines tumor necrosis factor-alpha, monocyte chemoattraction protein and macrophage inflammatory protein by more than 50% [25]. Cord blood stem cells can also limit or inhibit caspase expression and the caspase cascade in the myocardium that otherwise contributes to myocardial inflammation and myocyte death after coronary artery occlusion [26].…”
Section: Hucbc Mechanisms Of Actionmentioning
confidence: 99%
“…By stimulating fibroblast migration into infarctions and increasing collagen production, chitosan can increase infarct scar thickness which we observed in the present investigation. Increased scar thickness, especially in the infarct perimeter, can also limit the seepage of pro-introphils by 75% and lymphocytes by more than 50% that otherwise release inflammatory cytokines that cause myocardial inflammation and necrosis [25,27].…”
Section: Chitosan Mechanisms Of Actionmentioning
confidence: 99%
“…Implantation of HUCB cells into infarcted myocardium of non-immunosuppressed rats within 2 or at 24 hours after LAD occlusion, limited the expression of pro-inflammatory cytokines such as TNF-α, MCP-1, MIP-1α, and IFN-γ in the infarcted myocardium and it may be associated with significant decreases in infarct volume. Further analysis was carried out by transplanting 4 x 10 6 cells and performing cytokine analysis and inflammatory cell recruitment at 2, 6, 12, 24 and 72 hours after LAD ligation (Henning et al, 2008). They observed that the infiltration of inflammatory cells and secretion of inflammatory cytokines was significantly reduced by HUCB cells within 2 hours compared to non-treatment after LAD occlusion and this was maintained through to 72 hours.…”
Section: Intramyocardial Injectionmentioning
confidence: 99%